2019
DOI: 10.1097/tp.0000000000002491
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation Trends and Outcomes for Hereditary Hemorrhagic Telangiectasia in the United States

Abstract: Background. Liver arteriovenous malformations (AVM) in hereditary hemorrhagic telangiectasia (HHT) can necessitate liver transplantation. There is limited data on HHT patients undergoing liver transplantation (LT) in the United States. Methods. Two sources of data were used: (1) Scientific Registry of Transplant Recipients (SRTR) database (1998-2016) (2) Single center liver transplant database (Mayo Clinic Rochester, MN). The aims of this study were (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 22 publications
2
20
0
1
Order By: Relevance
“…Moreover, 14 (60.8%) out of 23 of patients with high-output heart failure and all cases (n = 12) of isolated symptomatic biliar disease from the European Liver Transplant Registry were females, similar to our observation [24]. In fact, decompensated high output cardiac failure and biliary complications are the most frequent causes of liver transplantation [24,[32][33][34]. Similar to previous studies, among patients with genotype data available from our cohort, those at high risk of harboring clinically significant liver disease had ACVRL1 mutation [6,19].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Moreover, 14 (60.8%) out of 23 of patients with high-output heart failure and all cases (n = 12) of isolated symptomatic biliar disease from the European Liver Transplant Registry were females, similar to our observation [24]. In fact, decompensated high output cardiac failure and biliary complications are the most frequent causes of liver transplantation [24,[32][33][34]. Similar to previous studies, among patients with genotype data available from our cohort, those at high risk of harboring clinically significant liver disease had ACVRL1 mutation [6,19].…”
Section: Discussionsupporting
confidence: 87%
“…In fact, the Simple Clinical Scoring Index included female gender as a risk factor for developing clinically significant hepatic involvement [19]. This female predominance in prevalence and severity of liver involvement is in agreement with the four published series of HHT patients with liver transplantation, where between 83.3 and 92.8% of the patients were women [24,[32][33][34]. Moreover, 14 (60.8%) out of 23 of patients with high-output heart failure and all cases (n = 12) of isolated symptomatic biliar disease from the European Liver Transplant Registry were females, similar to our observation [24].…”
Section: Discussionsupporting
confidence: 85%
“…LT offers successful therapy for HHT with liver involvement: 10-year patient survival rate reaches 86%. (2) PTEN loss of function leads to AVM by two mechanisms: one directly attributable to a PTEN mutation and another that involves genes that modulate PTEN activity. Several studies have shown that PTEN negatively regulates the phosphoinositide-3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signaling pathway by reversing the action of PI3K.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in cardiac function and normalization of hemodynamics have been demonstrated in patients with HHT transplanted for HOHF ( 15‐17 ) (Table 2).…”
Section: Diseases That Affect Both the Liver And Lungsmentioning
confidence: 99%